Thermal decomposition study of electrodeposited Fe-C and Fe-Ni-C alloys by differential scanning calorimetry - Haseeb, A.S. Md. Abdul; Arita, M.; Hayashi, Y. (Kluwer (now part of Springer), 2001)
Fe-0.96massC and Fe-15.4massNi-0.70massC alloys with hardness of 810 and 750 HV respectively have been electrodeposited at 50 degreesC from sulphate based baths containing a small amount of citric acid and L-ascorbic acid. Differential scanning calorimetry of the electrodeposited samples has been carried out in the temperature range of 293-725 K in argon atmosphere. Electrodeposited pure Fe is also investigated for comparison purposes. The DSC curves of both alloys contain two exothermic peaks: at about 411 K and 646 K for the Fe-C alloy, and 388 K and 639 K for the Fe-Ni-C alloy. These peaks are irreversible and do not appear during a second thermal cycling. The lower temperature peaks (designated as I) have been attributed mainly to the formation of epsilon/eta -Fe2C (first stage of tempering), while the higher temperature peaks (designated as III) are ascribed predominantly to theta -Fe3C formation (third stage of tempering). The presence of these peaks in the DSC curves confirms that electrodeposited Fe-C and Fe-Ni-C alloys are in a metastable state, where carbon atoms are entrapped in the iron lattice. The decomposition sequence of electrodeposited Fe-C and Fe-Ni-C alloys is found to follow the same general pattern as that of thermally prepared martensite. Attempt has been made to estimate the activation energy values for the reactions associated with the DSC peaks of the electrodeposited alloys and these values are compared with the available data on thermally prepared martensite. (C) 2001 Kluwer Academic Publishers.